Determinants of depression among individuals aged 15 years and older with hypertension (Analysis of Indonesian Health Survey Data 2023) - Rindu Desilva Nabila; Muhammad Syukri; Helmi Suryani Nasution; Adelina Fitri (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Depression among hypertension patients leads to low medication adherence and increases morbidity and suicidal ideation. Purpose: To analyze the determinants of depression among hypertension patients. Method: A secondary data analysis study used data from the Indonesian Health Survey in 2023 with a cross-sectional design. The population in this study was hypertensive patients aged 15 years and above in Indonesia. Data analysis was performed using SPSS using the Complex Sample Chi-Square and Logistic Regression statistical tests. Results: The prevalence of depression in hypertension patients was 2.9% (95% CI: 2.6% - 3.3%). Statistically significant variables were age 15-44 years [Adj. POR = 1.93 (95% CI: 1.34 - 2.78)], female [Adj. POR = 1.66 (95% CI: 1.10 - 2.50)], and having a chronic disease [Adj. POR = 2.36 (95% CI: 1.92 – 2.90)], smoking daily [Adj. POR = 2.83 (95% CI: 1.90 – 4.24)], not working [Adj. POR = 1.49 (95% CI: 1.17 – 1.90)], primary education [Adj. POR = 2.30 (95% CI: 1.44 – 3.67)], and not having a partner [Adj. POR = 1.55 (95% CI: 1.24 – 1.93)]. Conclusion: Daily smoking is a dominant factor in the occurrence of depression among people with hypertension. Suggested to people with hypertension pay more attention to their mental health. Please immediately check health screening and quit smoking to prevent depression. Keywords: Depression; Indonesian Health Survey (IHS); Hypertension; Smoking.